Organoids in the Clinic: A Systematic Review of Outcomes - Hofmann, Bjørn; Zinöcker, Severin; Holm, Søren; Lewis, Jonathan; Kavouras, Panagiotis (Cells, tissues, organs, 2023)
Research on organoids has undergone significant advances during the last decade. However, outcomes from the use of organoids in clinical trials have not yet been documented. Therefore, there is an urgent need to assess the reporting of clinically relevant outcomes from organoid research in the scientific literature. This article presents a systematic review and appraisal of the published literature in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, together with a synopsis of recent relevant reviews. Surprisingly, no randomized controlled trials have reported clinical outcomes with any types of organoids. We found very few ongoing and registered studies that may provide clinically relevant results within this decade. Our screening and interpretation of the literature, including review articles, indicate a focus on technical and preclinical aspects of organoid research. This is the first systematic review of clinical trials involving organoids. Few clinical studies are planned or already underway, and, so far, no high-quality evidence relating to the clinical outcomes of organoid research has been published. The many promises of organoid research still need to be translated from bench to bed.